An assessment of price convergence between natural gas and solar photovoltaic in the U.S. electricity market. Issue 3 (15th December 2016) - Nyangon, Joseph; Byrne, John; Taminiau, Job
Abstract : The U.S. shale boom has exerted downward pressure on natural gas prices nationally, widened oil‐to‐gas price spreads, and accelerated coal‐to‐gas fuel substitution. One concern is the impact of the rising production of shale gas on further development of a domestic solar photovoltaic (PV) market. Specifically, will lower natural gas prices slow or even reverse the current rapid growth in the solar market? Using the Phillips–Sul convergence test, this paper investigates whether the levelized cost of energy (LCOE) of solar PV and natural gas electricity generation in the United States have converged. Using weekly Henry Hub‐linked natural gas spot prices and utility PV system prices from 2010 to 2015, empirical tests for convergence are applied to examine the extent of spot market integration and the speed with which market forces move the two energy prices toward equilibrium. The paper also assesses the link between the MAC Solar Energy Index (SUNIDX) and the S&P GSCI natural gas index spot prices for evidence of market integration during 2007–2015. We conclude that PV and natural gas prices are not converging, and the two markets are not integrated nationally, but some level of integration could exist at regional and state levels that will need to be tested in future research. We also conclude that complementary use of the technologies is likely; while price convergence is not likely to occur soon, distinctive complementary benefits of each resource compared to each other (e.g., fast‐start capabilities for gas and low price volatility for PV) will offer opportunities that expand market demand for both. WIREs Energy Environ 2017, 6:e238. doi: 10.1002/wene.238 This article is categorized under: Photovoltaics > Economics and Policy Energy Systems Economics > Systems and Infrastructure Abstract : Shale gas boom in Pennsylvania is a major driver of strong growth in natural gas production in counties such as Washington, Bradford, and Susquehanna with positive effects on (a) gas spot prices, (b) wages and local business activity, and (c) economic diversification and infrastructure development. A multidimensional market perspective is applied to study natural gas and solar PV markets in the United States for evidence of price convergence and integration using Phillips‐Sul convergence test and Kalman filter time‐varying analysis as well as assessing the performance of MAC Global Solar Energy Index (SUNIDX) and S&P GSCI (natural gas) indices. Modeled LCOE for solar PV and natural gas systems average 12.95¢/kWh and 9.5¢/kWh, respectively.